Unemployment and Political Extremism in Zimbabwe, 2000- 2010 - Sitima, Innocent (Journal of Economics and Behavioral Studies, 2013)
Unemployment prevalence among the youth is largely tribute to political extremism in politically disoriented countries. The paper examined the effects of political extremism in Zimbabwe on the high unemployment statistics in the period between 2000- 2010. The study applies the Zimbabwean quarterly data to explore the relationship among variables by using interrelated Tobit econometric procedure. The study findings indicated that 82.97 percent of the Zimbabwean population is unemployed, if the country is unstable and there is political violence. The partial coefficients showed that when political extremism persists, and is not controlled, unemployment is likely to increase by almost 4.29 percent increase in each period.